Drivers Influencing Consumersâ€™ Adoption of Over-the-Top Video Streaming Platforms: An Exploratory Sequential Analysis - Garg, Pratibha; Gupta, Neha (Indian Journal of Marketing, 2025)
Purpose : The present study focused on evaluating the drivers influencing the consumerâ€™s selection of over-the-top (OTT) video platforms in India. The popularity of streaming services has been increasing worldwide and has changed the media industryâ€™s traditional practices in terms of patterns, means, and quality because of technological innovation. Streaming platforms are now widely seen as the entertainment industryâ€™s future. OTT platforms are becoming more and more popular because they connect people through different streaming platforms and provide high-quality content. Methodology : The drivers influencing the consumerâ€™s selection of OTT video platforms in India were evaluated using an exploratory sequential approach (ESA). Under ESA, the study was conducted in three phases. Phase I identified and finalized the drivers through an extensive literature review and expertsâ€™ opinions. In Phase II, a fuzzy analytical hierarchy process was utilized to determine the priority weightage of the OTT drivers, while Phase III checked the robustness of the results by conducting sensitivity analysis. Findings : This study found that consumersâ€™ adoption of OTT video platforms is primarily determined by two drivers: â€œperceived enjoymentâ€ and â€œsocial influence.â€ The driver â€œperceived enjoymentâ€ was found to be substantially influential. In addition, binge-watching, convenience, and relaxation were found to be predictors of usersâ€™ selection of OTT platforms. It was found that several online streaming platforms were well-liked and provided excellent content with a lot of options, few commercials, availability, and accessibility through laptops, tablets, and smartphones with a ton of features at an affordable price. Practical Implications : This studyâ€™s findings will provide indispensable insights to market analysts and decision-makers to formulate strategies for future market opportunities. Originality : Unlike prior research on consumer adoption of OTT video streaming platforms, the current work intended to research the most effective factors influencing the criteria for consumersâ€™ selection of OTT video platforms in India using an ESA.